Chordoma – treatment and prognosis - Kowalska, Berta; Goździewicz, Jacek; Lisiecki, Janusz; Kłosiński, Piotr (Contemporary Oncology/Współczesna Onkologia, 2003)
The work has been presented current views upon the origins, diagnosis and methods of treatment of chordoma in the material of the Trauma – Orthopeadics and Neuroorthopaedics Department of L. Rydygier Hospital in Cracow. There were three cases of chordoma operated on, two of which were connected with the cervical spine and one – with the lumbal spine. All of the patients were directed to our department from clinics with untypical deficit symptoms. Each case was fully diagnosed, including MRI as well as precise physical examination. The patients were qualified to be operated on according to increasing neurological symptoms. The general condition of the patients, their qualifications for operation and diagnostics were presented. In both cases of cervical spine laminectomy applied with the subtotal excision and stabilisation with CCD (Sofamor Danek) have been performed. In the lumbal spine case, after laminectomy and excision, total vertebral replacement and transpedicular stabilisation have been done. The prognosis was determined by the characteristics and placement of the tumor and therefore difficulties with its total removal. Decompression of the spinal cord and infiltration structures, pain relief, treating neurological deficits were the main target of the operation after which the neurological condition of the patients improved and the progress of the illness was stopped. The patients have remained under observation for four, two and one year respectively. We observed gradual regrowing of the tumor, confirmed by MRI.